Method for preparing prebaked anode for aluminum by adding carbon fiber powder and polymerized asphalt

By adding carbon fiber powder and polymerized asphalt to the anode of the aluminum electrolytic cell, high-density and high-strength high-quality pre-baked anode was prepared, which solved the problems of low anode density and poor strength, and significantly improved its thermal shock resistance and service life in the aluminum electrolytic cell.

CN119553316APending Publication Date: 2025-03-04SHANDONG CHENYANG NEW CARBON MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411832633.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The pre-baked anode in the existing aluminum electrolytic tank has low density and poor strength, which leads to abnormal situations such as slag, blocks, and fragmentation in the electrolytic tank, affecting the normal production of the electrolytic tank and the stability of the tank condition.

Method used

Pre-baked anode for high-quality aluminum by adding carbon fiber powder and polymerized asphalt. The carbon fiber powder is mixed with the calcined coke aggregate in proportion, and polymerized asphalt is added, and after molding and high-temperature roasting treatment, a high-quality pre-baked anode is prepared.

Benefits of technology

The density, strength, conductivity and other properties of the pre-baked anode are improved, the comprehensive performance of the anode is enhanced, the thermal shock resistance in the aluminum electrolytic cell is enhanced, the slag and block drop of the anode is reduced, the power consumption and carbon consumption are reduced, and the anode usage cycle is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005185909230000081
    Figure BDA0005185909230000081
  • Figure BDA0005185909230000082
    Figure BDA0005185909230000082
Patent Text Reader

Abstract

The invention relates to a method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymerized asphalt, which comprises the following steps of: crushing, screening and grading calcined coke to obtain aggregates with various particle sizes and ball-milled powder; mixing the ground carbon fiber powder and the calcined coke, adding the mixture into a mixing and kneading pot for mixing and kneading, preheating, adding the polymerized asphalt, and continuously heating and mixing and kneading to obtain a paste material; putting the obtained paste into a mold in batches for extrusion forming, and performing cooling forming to obtain a prebaked anode green body; and putting the cooled and molded prebaked anode green body into a roasting furnace, roasting according to a heating curve, and naturally cooling to obtain a high-quality prebaked anode finished product. Compared with the prior art, the prebaked anode has the following beneficial effects that the volume density and mechanical strength of a prebaked anode green body can be effectively improved, the volume density, compression strength and conductivity of the prebaked anode are improved, the thermal shock resistance of the prebaked anode in an aluminum electrolysis cell is improved, and the resistivity and air permeability of the anode are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminum electrolysis in nonferrous metal metallurgy, and in particular to a method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymerized asphalt. Background Art

[0002] Due to the continuous development of large-scale aluminum electrolytic cells in China, 400-600KA aluminum electrolytic cells have become the mainstream cell type in the electrolytic aluminum industry. The rapid development of high-current intensity electrolytic cells has also put forward higher requirements on the quality of the anode material of the electrolytic cell - pre-baked anodes for aluminum. If the pre-baked anode has low density and poor strength, it will cause abnormal conditions such as slag falling, block falling, and fragmentation of the anode in the electrolytic cell, affecting the normal production of the electrolytic cell and the stability of the cell condition.

[0003] In order to solve one of the above problems, it is necessary to produce a high-quality prebaked anode for aluminum with high quality performance to withstand the impact of the strong magnetic field and thermal field in the electrolytic cell, reduce the occurrence of abnormal conditions such as slag falling, block falling, and fragmentation, and provide guarantee for the high current production of aluminum electrolytic cells. Summary of the invention

[0004] In view of the above deficiencies in the prior art, the technical problem to be solved by the present invention is: to provide a method for preparing high-quality prebaked anodes for aluminum by adding carbon fiber powder and polymer asphalt composite technology, so as to improve the density, strength, conductivity and other properties of the prebaked anode, and improve the comprehensive performance of the prebaked anode, so as to achieve the purpose of improving its thermal shock resistance in the aluminum electrolytic cell.

[0005] The method for preparing prebaked anodes for aluminum by adding carbon fiber powder and polymer asphalt described in the present invention is to use carbon fiber powder as an added raw material, mix it evenly with calcined coke as a prebaked anode aggregate in proportion, add polymer asphalt, and after molding and high-temperature baking, prepare a high-quality prebaked anode for aluminum with high-quality comprehensive performance.

[0006] The method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymerized pitch according to the present invention comprises the following specific steps:

[0007] S1: Preparation of calcined coke: First, petroleum coke is calcined at high temperature, and then the calcined coke is crushed, sieved and graded to obtain aggregates of various particle sizes and ball-milled powder;

[0008] S2: Preparation of paste: Grinding carbon fiber powder with a jet mill, mixing the ground carbon fiber powder with various particle size materials of calcined coke according to 1% to 2% of the mass of calcined coke, and adding the mixed powder into a kneading pot, kneading and preheating, and then adding polymerized asphalt, and continuing to heat and knead uniformly to obtain a paste, wherein the polymerized asphalt has a softening point of 110° C. to 115° C., a β resin content of 20% to 25wt%, and a coking value of 57% to 60wt%;

[0009] S3: Preparation of prebaked anode green body: the paste obtained in S2 is put into a mold in batches for extrusion molding, and after the molding is vibrated for a certain period of time, a prebaked anode green body is obtained;

[0010] S4: Preparation of prebaked anode finished products: The prebaked anode green body cooled and formed in S3 is placed in a baking furnace and baked according to a certain temperature rise curve. After baking, the temperature is naturally lowered to obtain a high-quality prebaked anode finished product.

[0011] Preferably, in step S1, the aggregate in the calcined coke and the ball-milled powder are subjected to the maximum packing density method and the compacted bulk density of different formulations is tested by orthogonal test to optimize the best dry material formulation.

[0012] Preferably, in step S1, the particle size and proportion of the optimal compacted bulk density dry material formula of aggregate and ball-milled powder in the calcined coke are: particle size of 8-3mm and coke content of 17-28wt%, particle size of 3-1mm and coke content of 22-33wt%, particle size of 1-0mm and coke content of 10-15wt%, and the content of ball-milled powder and dust collected powder with a particle size of less than 200 mesh (0.075mm) is 30-40wt%.

[0013] Preferably, in step S2, the carbon fiber powder has the characteristics of high strength and high conductivity.

[0014] Preferably, in step S2, the carbon fiber powder is ground by a jet mill, and the fineness is 200-400 meshes.

[0015] Preferably, in step S2, the preparation method of the polymerized asphalt is as follows: low-temperature coal tar and high-temperature modified asphalt are mixed in a mass ratio of 1:9 through a pipeline mixer, and then enter an asphalt tubular furnace for heating, the outlet temperature of the tubular furnace is set at 370-380°C, and then enter an asphalt reactor for thermal polymerization for 7-10 hours, and then enter a flash tower for flash evaporation, and finally obtain polymerized asphalt;

[0016] Preferably, in step S2, the ground carbon fiber powder and various particle size materials of calcined coke are mixed and added into a kneading pot for kneading and preheating, the kneading time is 15 to 25 minutes, and the preheating temperature is 145 to 155°C.

[0017] Preferably, in step S2, the polymerized asphalt heated to 190° C. is added into a kneading pot, and the heating and kneading are continued for 25 to 35 minutes, and after being uniformly mixed, a paste with a temperature of 170° C. is obtained.

[0018] Preferably, in step S3, the obtained prebaked anode green body has the characteristics of high volume and high density.

[0019] Preferably, in step S3, the compression molding vibration time is 60S, the molding temperature is 150°C, and the volume density of the prebaked anode green body is 1.640kg / cm 3 ~1.655kg / cm 3 ;

[0020] Preferably, in step S4, the prebaked anode green body after cooling and forming is placed in a baking furnace and baked according to a designed temperature rise curve, wherein the temperature is from room temperature to 300°C for 3h; 300°C-500°C for 2.5h; 500°C-750°C for 3h; 750°C-1000°C for 3h; 1000°C, kept warm for 2h; 1000°C-1160°C for 2.5h; 1160°C, kept warm for 3h; after the baking is completed, the temperature is naturally lowered to obtain a high-quality prebaked anode product, and the highest temperature of the high-quality prebaked anode product is 1050-1100°C.

[0021] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0022] (1) It can effectively improve the problem of low and large fluctuations in the bulk density of calcined coke, and improve and stabilize the tapped bulk density of the dry material formula after mixing materials of various particle sizes of calcined coke;

[0023] (2) It can effectively improve the plasticity and bonding properties of the anode paste and increase the volume density and mechanical strength of the prebaked anode green body;

[0024] (3) It can effectively improve the carbon residue rate of polymerized asphalt on prebaked anodes and reduce the anode burnout rate;

[0025] (4) It can effectively improve the volume density, compressive strength and conductivity of the prebaked anode, reduce the anode resistivity and air permeability, and achieve the purpose of producing high-performance and high-quality prebaked anodes;

[0026] (5) It can effectively improve the thermal shock resistance of prebaked anodes in aluminum electrolytic cells, reduce slag and block falling of anodes during electrolysis, reduce electricity consumption and carbon consumption per ton of aluminum, improve current efficiency, extend the service life of anodes, and stabilize the production and operation of aluminum electrolytic cells. DETAILED DESCRIPTION

[0027] The present invention is further described below by means of specific embodiments, but the present invention is not limited thereto. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

[0028] Example 1: The method for preparing the prebaked anode product is as follows:

[0029] 1. The particle size and proportion of calcined coke aggregate and ball-milled powder are as follows: the particle size is 8-3mm and the coke content is 23wt%, the particle size is 3-1mm and the coke content is 27wt%, the particle size is 1-0mm and the coke content is 12wt%, and the content of ball-milled powder and dust-collected powder with a particle size below 200 mesh (0.075mm) is 38wt%; the total weight of the calcined coke aggregate and ball-milled powder is 4000g;

[0030] 2. The softening point of the polymerized asphalt is 114.4°C, the toluene insoluble matter is 29.48wt%, the quinoline insoluble matter is 8.47wt%, the β resin content is 21.01wt%, and the coking value is 58.21wt%; the added amount is 760g;

[0031] 3. Add the mixture of calcined coke aggregate and ball mill powder into a kneading pot for kneading and preheating to 150°C, then add 190°C polymerized asphalt, continue heating and kneading for 20 minutes to obtain a paste at 170°C;

[0032] 4. The mixed paste is placed in batches into a mold for extrusion molding. The molding vibration time is 60S and the molding temperature is 150°C. The volume density of the obtained pre-baked anode green body is 1.640kg / cm 3 -1.645kg / cm 3 ;

[0033] 5. Place the cooled and formed prebaked anode green body in a baking furnace and bake it according to the designed temperature rise curve: from room temperature to 300°C for 3h; 300°C-500°C for 2.5h; 500°C-750°C for 3h; 750°C-1000°C for 3h; 1000°C, keep warm for 2h; 1000°C-1160°C for 2.5h; 1160°C, keep warm for 3h; after baking, cool down naturally to obtain the prebaked anode finished product.

[0034] Example 2: A method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymerized pitch, the steps are as follows:

[0035] 1. The particle size and proportion of calcined coke aggregate and ball-milled powder are as follows: the particle size is 8-3mm and the coke content is 23wt%, the particle size is 3-1mm and the coke content is 27wt%, the particle size is 1-0mm and the coke content is 12wt%, and the content of ball-milled powder and dust-collected powder with a particle size below 200 mesh (0.075mm) is 38wt%; the total weight of the calcined coke aggregate and ball-milled powder is 4000g;

[0036] 2. Grind the carbon fiber powder with a jet mill, and add the carbon fiber powder according to 1% of the mass of the calcined coke; the total amount of carbon fiber powder added is 40g;

[0037] 3. The softening point of the polymerized asphalt is 114.4°C, the toluene insoluble matter is 29.48wt%, the quinoline insoluble matter is 8.47wt%, the β resin content is 21.01wt%, and the coking value is 58.21wt%; the added amount is 760g;

[0038] 4. Mix the carbon fiber powder with the mixture of calcined coke aggregate and ball-milled powder, add it into a kneading pot for kneading and preheating to 150°C, then add 190°C polymerized asphalt, continue heating and kneading for 20 minutes to obtain a paste at 170°C;

[0039] 5. The mixed paste is placed in batches into a mold for extrusion molding. The molding vibration time is 60S and the molding temperature is 150°C. The volume density of the obtained pre-baked anode green body is 1.645kg / cm 3 -1.650kg / cm 3 ;

[0040] 6. Place the cooled and formed prebaked anode green body in a baking furnace and bake it according to the designed temperature rise curve: from room temperature to 300°C for 3h; 300°C-500°C for 2.5h; 500°C-750°C for 3h; 750°C-1000°C for 3h; 1000°C, keep warm for 2h; 1000°C-1160°C for 2.5h; 1160°C, keep warm for 3h; after baking, cool down naturally to obtain high-quality prebaked anode products.

[0041] Example 3: A method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymerized pitch, the steps are as follows:

[0042] 1. The particle size and proportion of calcined coke aggregate and ball-milled powder are as follows: the particle size is 8-3mm and the coke content is 23wt%, the particle size is 3-1mm and the coke content is 27wt%, the particle size is 1-0mm and the coke content is 12wt%, and the content of ball-milled powder and dust-collected powder with a particle size below 200 mesh (0.075mm) is 38wt%; the total weight of the calcined coke aggregate and ball-milled powder is 4000g;

[0043] 2. Grind the carbon fiber powder with a jet mill, and add the carbon fiber powder according to 1.5% of the mass of the calcined coke; the total amount of carbon fiber powder added is 60g;

[0044] 3. The softening point of the polymerized asphalt is 114.4°C, the toluene insoluble matter is 29.48wt%, the quinoline insoluble matter is 8.47wt%, the β resin content is 21.01wt%, and the coking value is 58.21wt%; the added amount is 760g;

[0045] 4. Mix the carbon fiber powder with the mixture of calcined coke aggregate and ball-milled powder, add it into a kneading pot for kneading and preheating to 150°C, then add 190°C polymerized asphalt, continue heating and kneading for 20 minutes to obtain a paste at 170°C;

[0046] 5. The mixed paste is placed in batches into a mold for extrusion molding. The molding vibration time is 60S, the molding temperature is 150℃, and the volume density of the obtained pre-baked anode green body is 1.650kg / cm 3 -1.655kg / cm 3 ;

[0047] 6. Place the cooled and formed prebaked anode green body in a baking furnace and bake it according to the designed temperature rise curve: from room temperature to 300°C for 3h; 300°C-500°C for 2.5h; 500°C-750°C for 3h; 750°C-1000°C for 3h; 1000°C, keep warm for 2h; 1000°C-1160°C for 2.5h; 1160°C, keep warm for 3h; after baking, cool down naturally to obtain high-quality prebaked anode products.

[0048] Example 4: A method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymerized pitch, the steps are as follows:

[0049] 1. The particle size and proportion of calcined coke aggregate and ball-milled powder are as follows: the particle size is 8-3mm and the coke content is 23wt%, the particle size is 3-1mm and the coke content is 27wt%, the particle size is 1-0mm and the coke content is 12wt%, and the content of ball-milled powder and dust-collected powder with a particle size below 200 mesh (0.075mm) is 38wt%; the total weight of the calcined coke aggregate and ball-milled powder is 4000g;

[0050] 2. Grind the carbon fiber powder with a jet mill, and add the carbon fiber powder according to 2% of the mass of the calcined coke; the total amount of carbon fiber powder added is 80g;

[0051] 3. The softening point of the polymerized asphalt is 114.4°C, the toluene insoluble matter is 29.48wt%, the quinoline insoluble matter is 8.47wt%, the β resin content is 21.01wt%, and the coking value is 58.21wt%; the added amount is 760g;

[0052] 4. Mix the carbon fiber powder with the mixture of calcined coke aggregate and ball-milled powder, add it into a kneading pot for kneading and preheating to 150°C, then add 190°C polymerized asphalt, continue heating and kneading for 20 minutes to obtain a paste at 170°C;

[0053] 5. The mixed paste is placed in batches into a mold for extrusion molding. The molding vibration time is 60S and the molding temperature is 150°C. The volume density of the obtained pre-baked anode green body is 1.640kg / cm 3-1.645kg / cm 3 ;

[0054] 6. Place the cooled and formed prebaked anode green body in a baking furnace and bake it according to the designed temperature rise curve: from room temperature to 300°C for 3h; 300°C-500°C for 2.5h; 500°C-750°C for 3h; 750°C-1000°C for 3h; 1000°C, keep warm for 2h; 1000°C-1160°C for 2.5h; 1160°C, keep warm for 3h; after baking, cool down naturally to obtain high-quality prebaked anode products.

[0055] Comparative Example: The preparation method of the prebaked anode product is as follows:

[0056] 1. The particle size and proportion of calcined coke aggregate and ball-milled powder are as follows: the particle size is 8-3mm and the coke content is 23wt%, the particle size is 3-1mm and the coke content is 27wt%, the particle size is 1-0mm and the coke content is 12wt%, and the content of ball-milled powder and dust-collected powder with a particle size below 200 mesh (0.075mm) is 38wt%; the total weight of the calcined coke aggregate and ball-milled powder is 4000g;

[0057] 2. The softening point of the modified asphalt is 105.8°C, the toluene insoluble matter is 27.58wt%, the quinoline insoluble matter is 7.56wt%, the β resin content is 20.02wt%, and the coking value is 55.82wt%; the addition amount is 760g;

[0058] 3. Add the mixture of calcined coke aggregate and ball-milled powder into a kneading pot for kneading and preheating to 140°C, then add 180°C polymerized asphalt, continue heating and kneading for 20 minutes to obtain a paste at 160°C;

[0059] 4. The mixed paste is placed in batches into a mold for extrusion molding. The molding vibration time is 60S and the molding temperature is 145°C. The volume density of the obtained pre-baked anode green body is 1.635kg / cm 3 -1.640kg / cm 3 ;

[0060] 5. Place the cooled and formed prebaked anode green body in a baking furnace and bake it according to the designed temperature rise curve: from room temperature to 300°C for 3h; 300°C-500°C for 2.5h; 500°C-750°C for 3h; 750°C-1000°C for 3h; 1000°C, keep warm for 2h; 1000°C-1160°C for 2.5h; 1160°C, keep warm for 3h; after baking, cool down naturally to obtain the prebaked anode finished product.

[0061] 1. Performance testing

[0062] The finished products of the above-mentioned embodiments 1-4 and the control example were sampled, and the prebaked anode performance parameters were analyzed according to the industry standard YS / T285-2022. The results are shown in Table 1.

[0063] Table 1 Comparative Example and Example 1-4 Prebaked Anode Performance Test Results

[0064]

[0065] The results show that the prebaked anodes prepared in Examples 1-4 have significantly better quality indicators than the performance parameters of the common prebaked anodes prepared in the control example, especially the anode of Example 3 has the best indicators. Therefore, Example 3 can be used as the preferred solution for industrial production applications.

[0066] 2. Industrial production and application

[0067] Example 3 adopts a method for preparing high-quality prebaked anodes for aluminum by adding carbon fiber powder and polymer asphalt. By applying it in the industrial production of anodes, the purpose of producing high-quality prebaked anodes is achieved.

[0068] Table 2 Test results of conventional indicators of anodes produced in industrialized production in Example 3

[0069]

[0070] Note: TY-1 is the first-grade product requirement of the prebaked anode standard YS / T 285 for aluminum electrolysis

[0071] The experimental results of the above performance tests and the comparison of anode industrial applications show that:

[0072] (1) Example 3 The high-quality prebaked anode prepared by the method of preparing a prebaked anode for aluminum by adding carbon fiber powder and polymerized asphalt as described in the present invention has greatly improved quality performance compared with the ordinary prebaked anode produced by traditional modified asphalt. The addition of carbon fiber powder can better fill the gaps between the calcined coke aggregate particles and the open pores inside the aggregate particles, improve the density, strength and conductivity of the prebaked anode, and reduce the air permeability of the anode; polymerized asphalt, due to its high coking value and high β resin content, can effectively improve the adhesion and residual carbon rate of the binder asphalt to the carbon anode, reduce the anode burnout, and further improve the density and mechanical strength of the anode.

[0073] (2) Example 3 is a high-quality prebaked anode prepared by the method of the present invention, and its physical and chemical properties are significantly better than the requirements of the first-class products of the industry standard. The high-quality anode with high density, high strength, high conductivity and high thermal shock resistance developed and produced by this composite technology can withstand a larger current density when used under the same conditions of the current domestic large-scale aluminum electrolytic cell production, which is conducive to the intensification of current in electrolytic production and the increase of aluminum production; at the same time, it can also effectively reduce the carbon consumption and power consumption of the anode, and the residual pole after electrolysis has high hardness, high regularity and less carbon slag, which has a positive contribution to promoting energy conservation and consumption reduction in the electrolytic aluminum industry.

[0074] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

[0075] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymer pitch, characterized in that: The steps include: S1: Preparation of calcined coke: First, petroleum coke is calcined at high temperature, and then the calcined coke is crushed, sieved and graded to obtain aggregates of various particle sizes and ball-milled powder; S2: Preparation of paste: Grind the carbon fiber powder with a jet mill, mix the ground carbon fiber powder with various particle size materials of the calcined coke according to 1% to 2% of the mass of the calcined coke, and add it into a kneading pot. After kneading and preheating, add polymerized asphalt, continue heating and kneading to obtain a paste. The polymerized asphalt has a softening point of 110°C to 115°C, a β resin content of 20% to 25 wt%, and a coking value of 57% to 60wt%; S3: Preparation of prebaked anode green body: the paste obtained in S2 is put into a mold in batches for extrusion molding, and after the molding is vibrated for a certain period of time, a prebaked anode green body is obtained; S4: Preparation of prebaked anode finished products: The prebaked anode green body cooled and formed in S3 is placed in a baking furnace and baked according to a certain temperature rise curve. After baking, the temperature is naturally lowered to obtain a high-quality prebaked anode finished product.

2. The method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymer pitch according to claim 1, characterized in that: In the step S1, the particle size and proportion of the optimal compacted bulk density dry material formula of the aggregate and the ball-milled powder in the calcined coke are: the particle size is 8-3mm and the coke content is 17-28wt%, the particle size is 3-1mm and the coke content is 22-33wt%, the particle size is 1-0mm and the coke content is 10-15wt%, and the ball-milled powder and dust collection powder with a particle size below 200 mesh have a content of 30-40wt%.

3. The method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymer pitch according to claim 1, characterized in that: In the step S2, the carbon fiber powder is ground by a jet mill, and the fineness is 200-400 mesh.

4. The method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymer pitch according to any one of claim 3, characterized in that: In the step S2, the ground carbon fiber powder and the various particle size materials of the calcined coke are mixed and added into a kneading pot for kneading and preheating. The kneading time is 15-25 minutes, and the preheating temperature is 145-155°C.

5. The method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymer pitch according to claims 1-4, characterized in that: In the step S2, the polymerized asphalt heated to 190° C. is added into a kneading pot, and the kneading is continued for 25 to 35 minutes. After the mixture is uniformly mixed, a paste having a temperature of 170° C. is obtained.

6. The method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymer pitch according to claim 5, characterized in that: In step S3, the compression molding vibration time is 60S, the molding temperature is 150°C, and the volume density of the prebaked anode green body is 1.640 kg / cm 3 ~1.655kg / cm 3 .

7. The method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymer pitch according to claim 1, characterized in that: In step S2, the preparation method of the polymerized asphalt is as follows: low-temperature coal tar and high-temperature modified asphalt are mixed in a mass ratio of 1:9 through a pipeline mixer, and then enter an asphalt tubular furnace for heating. The outlet temperature of the tubular furnace is set at 370~380°C, and then enter an asphalt reactor for thermal polymerization reaction for 7~10 hours, and then enter a flash tower for flash evaporation to finally obtain polymerized asphalt.

8. The method for preparing a prebaked anode for aluminum by adding carbon fiber powder and polymer pitch according to claim 7, characterized in that: In the step S4, the prebaked anode green body after cooling and forming is placed in a baking furnace and baked according to the designed temperature rise curve, wherein the temperature is from room temperature to 300°C for 3 hours; 300°C-500°C for 2.5 hours; 500°C-750°C for 3 hours; 750°C-1000°C for 3 hours; 1000°C, kept warm for 2 hours; 1000°C-1160°C for 2.5 hours; 1160°C, kept warm for 3 hours; after the baking is completed, the temperature is naturally lowered to obtain a high-quality prebaked anode finished product.